Translocation of meadow, heath and fen to the Habitat Garden: The first insights after 4 years of the experiment. Issue 1 (22nd November 2018) - Nowak, Arkadiusz; Maślak, Magdalena; Smieja, Agata; Góra, Julia; Kojs, Paweł; Nowak, Sylwia; Nobis, Marcin
Abstract: Questions: How does species composition of different vegetation types respond to translocation? How do they respond to encroachment of expansive native or alien species? Location: Meadow, heath and fen plots in Radzionków Habitat Botanical Garden, Poland. Methods: In 2013, between June and October, 16, 500 pieces of turf blocks from three communities, each 80 × 120 cm in size and 40–50 cm deep, were transferred from a donor site to newly constructed artificial basins. Temporal changes of species composition were observed in 163 permanent plots 2 × 2 m from 2013 to 2016. To analyse compositional changes, we carried out constrained ordination with time as explanatory variable. For changes in species richness, diversity, herb and shrub layers, contribution of woody species, diagnostic taxa, archaeophytes, neophytes, native expansive taxa and ruderal plants, a one‐way ANOVA was applied. Results: We found that only 35%–39% of species had a positive correlation with time. The total number of species significantly decreased only within the meadow plots. The fen and heath only experienced a slight decrease in species number. Significant changes in abundance of diagnostic species were observed in all plant communities. The abundances of diagnostic taxa were maintained during the first 2 year, then dropped considerably. The highest decrease was noted in the heathland community. Conclusions: Turf translocation appeared to be only partially effective as a compensatory measure. Four years after the translocation, the three different habitats still maintained their specific structural features, however the number of diagnostic taxa considerably decreased, particularly in the heathland and the wet meadow. Given the high financial and logistical effort required, translocation measures are questionable and should only be applied as an exceptional last resort method. Abstract : We analysed the changes in species composition in meadow, heath and fen plots after translocation to artificial basins in Habitat Botanical Garden. After 4 years of experiment we found that the most sensitive vegetation type in terms of species decrease was meadow. All habitats suffer from diagnostic species decline with heathland as the most impoverished. Despite the three plant communities still maintained their specific structural features, turf translocation appeared only partially to be an effective compensatory measure. Given the high financial and logistical effort translocations remain controversial and should only be applied as exceptional last chance method.